Over a million students use our free study notes to help them with their homework
X^2 - (4*3) + 8 = 0 X^2 -4 = 0 X^2 = 4 X = 2
There's a lot of information to take on in this question so it's firstly important to isolate the facts: ...
Step 1: x+y=7 can be rearranged as: x= 9 - y.Step 2: We substitute the expression of x in the second equation: 9 - y - 2y + 1 = 1Step 3: We calculate the value of y. 9 + 1 - 1- 3y=0. It is equivalent with...
Step 1- Workout how many people overall said yes. We Know overall there are 200 people and of these 200 people 1/4 said yes. Therefore, we need to workout 1/4 of 200. Simply divide 200 by 4. 200/4=5...
First, I would label the two equations 1 and 2:(1) 3x+by=5(2)x-y=-2Next, multiply (2) by 3 and subtract this equation from (1) in order to cancel out the x terms: 3x+by=5-(3x-3y=-6)This results in the equ...
←
369
370
371
372
373
→
Internet Safety
Payment Security
Cyber
Essentials